Psychology Profile Of Adolsecent In Malaysia. - See, Ching Mey (2006)
The Psychological Needs Profile Inventory for Adolescents is a inventory deveioped to identify the positive and negative behaviors of the adolescents, and the reasons for behavlng positively or negatively. This rnventory is also used to identify adolescents who are at-risk with psychological disorders.